Examination of the apricot variety use and the factors affecting variety use in the Gönc production area - D. D. Nagyné; J. Nyéki; M. Soltész; Z. Szabó (International Journal of Horticultural Science, 2010)
Hungary is a traditional fruit growing country for ages. As fruit sector has a very high hand work request and value added, it has an important role to decrease the elimination of unemployment and the lack of income in the disadvantage rural areas. The study was made in the year of 2009, the studied population consisted of the members of the fruit-grower marketing organization (Gyümölcsért Ltd.), that organizes growing and sales of stone fruits in Hungary. The studied area of this Ltd is in North Hungary. The growers, who filled the questionnaire, were selected random simple sample. Two data collection were used during our research work: primer and secondary data collection. The resources of the primer data-collection were the questionnaires of our empirical survey that have been completed by the relevant information from informal interviews with farmers (who previously filled the questionnaires in). We introduced and analysed the local (county level) and the wider (region level) farming conditions by the secondary data. By the composition of the questions both qualitative and quantitative methods have been used. This current study intends to represent one part of this comprehensive research.We wish to briefly introduce mainly the research results concerning variety use.